Effect of polymer melt wall slip on the flow balance of profile extrusion dies - Carneiro, O. S. (2013)
This work describes the implementation of the wall slip boundary condition in an in-house developed 3D numerical code based on the Finite Volume Method. For this purpose, several phenomenological models relating the velocity and the shear stress at the wall were implemented. This new feature is verified using a simple case study, by comparing the numerical results with those obtained through the corresponding analytical solution. Then, the potentialities of the new code are illustrated performing flow simulations of a polymer melt in a complex flow channel. The results obtained show that the slip at the wall influences the flow distribution at the die flow channel outlet. Therefore, and to assess the relevance of slippage in the optimal die geometry, the automatic optimization of a die flow channel, required for the production of a specific thermoplastic profile, is performed using both the no-slip and slip boundary conditions, together with two alternative optimization strategies. It is shown that slip favors the flow balance of the dies and also other issues of its performance.